INVESTIGATING ELECTRICITY CONSUMPTION IN OGUN STATE, NIGERIA - BAMIDELE BADEJO; OLASUNKANMI OMOWUMI; NATHANIEL OGUNSEYE (Journal of Engineering Studies and Research)
This study examined electricity consumption in a Nigeria township with a view of understanding the challenges faced by electricity consumers and to proffer practicable suggestions for sustainable electricity supply. Major findings emanating from the study show that 26.7 % of respondents acknowledged the electricity supply through the electricity service provider (ESP). Again, 71 % of respondents relied on electricity through the alternative’s sources complementing ESP services. Furthermore, 75 % of respondents confirmed a temporal supply of 5 hours daily representing 20 % daily electricity supply. In another dimension, in terms of billing, 62.4 % received estimated electricity bills as many homes are without electricity meters. Finally, this study revealed some planning and policy implications and provided recommendations through which electricity consumption in the state could be improved upon.